Atypical presentation of congenital diaphragmatic hernia: case report - Arora, Sunita; Kaur, Gurpreet (International Journal of Contemporary Pediatrics, 2019)
The Congenital diaphragmatic hernia generally presents with severe respiratory distress in the neonatal period and usually occurs once in every 2,000-3500 births. Late-presenting congenital diaphragmatic hernia (CDH) has been defined as CDH diagnosed after the neonatal period due to initial symptoms after the neonatal period or asymptomatic CDH found in the course of routine X-ray examination of the chest beyond the neonatal period. When late presentations occur, patients may be asymptomatic or may be critically ill with unusual respiratory and gastrointestinal symptoms. Case characteristics: 3yrs old female child presented with history of pain abdomen, abdominal distension, vomiting, respiratory distress and fever since 5days. Chest tube was inserted in view of left sided pleural effusion. Later on, diagnosed with diaphragmatic hernia. Outcome Child was operated, and diaphragmatic repair done and was discharged successfully after 38 days. Message: Congenital diaphragmatic hernia should be considered in the differential diagnosis of any child with unusual respiratory or gastrointestinal symptoms and abnormal chest radiographic findings.